Anti-hyperglycemic activity of Trichosanthes tricuspidata root extract - Srinivasan Kulandaivel; Pawan Bajpai; Thangavel Sivakumar (Bangladesh Pharmacological Society, 2013)
To evaluate the anti-diabetic activity of ethanolic extract of Trichosanthes tricuspidata root in alloxan induced diabetic rats and to perform the phyto-chemical screening. The extraction, preliminary phytochemical screening, anti-diabetic activity in alloxan induced diabetic rats by oral administration of extract (200 and 400 mg/kg b.w.), the blood glucose level and biochemical parameters like cholesterol, triglyceride, serum protein, SGPT, SGOT, and ALP were estimated. Phytochemical studies shows the presence of carbohy-drates, proteins, glycosides and terpenoids and the ethanolic extract of T. tricuspidata root significantly lowered the blood sugar level. The above findings justified the traditional claim of anti-diabetic activity in this plant.